Bioinspired Ultrastrong Solid Electrolytes with Fast Proton Conduction along 2D Channels. Issue 28 (6th June 2017) - He, Guangwei; Xu, Mingzhao; Zhao, Jing; Jiang, Shengtao; Wang, Shaofei; Li, Zhen; He, Xueyi; Huang, Tong; Cao, Moyuan; Wu, Hong; Guiver, Michael D.; Jiang, Zhongyi
Abstract : Solid electrolytes have attracted much attention due to their great prospects in a number of energy‐ and environment‐related applications including fuel cells. Fast ion transport and superior mechanical properties of solid electrolytes are both of critical significance for these devices to operate with high efficiency and long‐term stability. To address a common tradeoff relationship between ionic conductivity and mechanical properties, electrolyte membranes with proton‐conducting 2D channels and nacre‐inspired architecture are reported. An unprecedented combination of high proton conductivity (326 mS cm −1 at 80 °C) and superior mechanical properties (tensile strength of 250 MPa) are achieved due to the integration of exceptionally continuous 2D channels and nacre‐inspired brick‐and‐mortar architecture into one materials system. Moreover, the membrane exhibits higher power density than Nafion 212 membrane, but with a comparative weight of only ≈0.1, indicating potential savings in system weight and cost. Considering the extraordinary properties and independent tunability of ion conduction and mechanical properties, this bioinspired approach may pave the way for the design of next‐generation high‐performance solid electrolytes with nacre‐like architecture. Abstract : The advancement of solid electrolytes is severely impeded by the strong tradeoff relationship between ion‐conduction and mechanical properties. Through integrating 2D channels and "brick‐and‐mortar" architecture into one materials system, an unprecedented combination of high proton conductivity and superior mechanical strength are achieved. This intriguing design may pave the way for the bioinspired design of next‐generation high‐performance solid electrolytes.